2021
DOI: 10.1097/qai.0000000000002706
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Near Point-of-Care Early Infant Diagnosis in NAMPHIA to Improve Turnaround Times in a National Household Survey

Abstract: Background: In the population-based HIV impact assessment surveys, early infant diagnosis (EID) was provided to infants ,18 months without a prior diagnosis. For the Namibia population-based HIV impact assessment (NAMPHIA), the Gen-eXpert platform was assessed for the feasibility of near POC EID testing compared with the standard Roche COBAS AmpliPrep/ COBAS TaqMan (CAP/CTM) platform. Quality assurance measures and turnaround time were compared to improve EID results reporting.Methods: NAMPHIA participants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…For example, in Côte d’Ivoire where HIV-2 is prevalent, the differentiation of HIV-1 and HIV-2 infection was only made at the laboratory; the results were required to be returned to participants. In Kenya and Namibia, 12 GeneXpert (Cepheid, Sunnyvale, CA) was used for preliminary early infant diagnosis with CL confirmation because regional laboratories where SLs were hosted had existing capacity to run the tests. Each of these tests types was an additional data source for data collection and processing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Côte d’Ivoire where HIV-2 is prevalent, the differentiation of HIV-1 and HIV-2 infection was only made at the laboratory; the results were required to be returned to participants. In Kenya and Namibia, 12 GeneXpert (Cepheid, Sunnyvale, CA) was used for preliminary early infant diagnosis with CL confirmation because regional laboratories where SLs were hosted had existing capacity to run the tests. Each of these tests types was an additional data source for data collection and processing.…”
Section: Methodsmentioning
confidence: 99%
“…A staging database excluding all PII was set up in Google Drive within a G Suite for Education 12 instance to facilitate cleaning, merging, and preparing analytic data sets containing field-based and laboratory-based data, including data from household, SL, and CL, which were linked through unique PTIDs. The staging database was used to merge household and LDMS data twice a week in the DWH to order laboratory-based tests in the CL.…”
Section: Methodsmentioning
confidence: 99%
“…Other notable contributions on the laboratory front come from Domaoal et al who described improvements to early infant diagnosis and return of results, achieved through near point-of-care testing in the Namibia survey 18 and from Voetsch et al who demonstrated how antiretroviral drug testing, in addition to viral load as part of a recent infection testing algorithm, can improve the accuracy of incidence estimates by identifying those with a long-term infection who are on ART who were misclassified as recently infected. 19…”
mentioning
confidence: 99%
“…16 Bray et al explored the association between interview length and consent for blood testing in several countries and found that longer interviews did not necessarily result in lower consent rates for blood testing. 17 Other notable contributions on the laboratory front come from Domaoal et al who described improvements to early infant diagnosis and return of results, achieved through near point-of-care testing in the Namibia survey 18 and from Voetsch et al who demonstrated how antiretroviral drug testing, in addition to viral load as part of a recent infection testing algorithm, can improve the accuracy of incidence estimates by identifying those with a long-term infection who are on ART who were misclassified as recently infected. 19 Summary reports of preliminary findings and full final reports from each country survey can be accessed online.…”
mentioning
confidence: 99%